Kalevipoeg - Raitio, Konstantin, 1855-1924 (Salt Lake City, UT : Project Gutenberg, 2021)
"Kalevipoeg" by Konstantin Raitio is a collection of epic poetry written in the late 19th century. The work recounts the adventures of its titular hero, Kalevipoeg, the son of Kaleva, as he engages with themes of national identity, heroism, and ancient Finnish mythology. The narrative intertwines the lore and legends of the Estonian people, highlighting their cultural heritage and the significance of their ancestral tales. At the start of the tale, the introduction explores the cultural context surrounding Kalevipoeg and its connection to the Finnish epic "Kalevala." It discusses the importance of these mythical narratives in shaping national identity and pride among the Finnish and Estonian peoples. The opening portion describes the heroic lineage of Kaleva and sets the stage for the protagonist, Kalevipoeg, linking him to his ancestors and establishing the stakes for his impending adventures. The groundwork for the subsequent tales is laid out, mentioning the trials and tribulations Kalevipoeg is destined to face as a mighty figure amid the struggles for honor and kinship in a rich mythological landscape. (This is an automatically generated summary.)
Release date is 2021-01-16
Jari Koivisto
Keywords: Kreutzwald, Friedrich Reinhold, 1803-1882. Kalevipoeg